The Mutual Influence of Signals from the Location Monitoring Equipment and Technological Communication in the High-Frequency Path of Power Transmission Line - Minullin, Renat; Fardiev, Ilshat (International Journal of Engineering and Technology, 2018)
The paper describes the main characteristics of equipment used for technological communication by means of overhead electric transmission lines: high-frequency relay protection, command transmission of emergency control, high-frequency communication for the transmission of telemechanics and telephony signals, as well as equipment for a location equipment for monitoring the condition of electric transmission lines. The results of experimental studies on the mutual influence of the signals from the location monitoring equipment and technological communication in the high-frequency path of overhead transmission lines are presented.Â It shows a lack of effect of signals from location monitoring equipment on the work of technological communication equipment. Methods are proposed to reduce the influence of technological communication signals on the operation of location equipment: the method of signal accumulation and the method of digital filtering of signals. Analysis of the results of joint operation of the location monitoring equipment and high-frequency communication equipment under various conditions and operating modes on operating 35-330 kV overhead lines confirms their full compatibility. Â Â Â